Stress-strain state and loss of stability of anisotropic thermal coating under thermal shock - Lyukshin B. A.; Lyukshin P. A.; Bochkareva S. A.; Matolygina N. Yu.; Panin S. V. Sergey Viktorovich (2014, 2014)
Title screen